Simultaneous diagnosis of familial achalasia: report of two cases - Masato Hoshino; Nobuo Omura; Fumiaki Yano; Se Ryung Yamamoto; Minoru Matsuda; Katsuhiko Yanaga (Surgical Case Reports, 2017)
Abstract Background Achalasia is a rare disease with a morbidity of 1 in 100,000, for which the exact mechanism of pathogenesis has not been clarified due to the small total number of patients. We herein report on our experience with two cases of familial achalasia in which the involvement of genetic inheritance was suspected. Case presentation These cases consist of a man in his thirties and his mother in her sixties. The son consulted the Department of Gastrointestinal Medicine at our institute with dysphagia, and an upper gastrointestinal endoscopy revealed a gastric submucosal tumor with a maximal diameter of approximately 50 mm. Achalasia was also strongly suspected due to the enlargement of the esophagus to the maximum transverse diameter of 55 mm by esophagography along with delayed clearance of barium. A detailed interview revealed prolonged mild dysphagia in his mother. Therefore, high-resolution manometry was carried out in both patients. As a result, peristaltic disorder was observed in the esophageal body in both the mother and son, leading to a definitive diagnosis of achalasia. For the son, total gastrectomy including the lower esophagus with Roux-en-Y reconstruction was performed. His postoperative course was uneventful, and the patient was discharged from hospital in remission on the 9th day following surgery and is currently undergoing follow-up as an outpatient. Conclusions We hereby report on a very rare case of familial achalasia that we experienced which may suggest a genetic element in the onset of achalasia, and reviewed the literature.